Avaliação da sensibilidade de diferentes testes diagnósticos para a dengue - Souza, Camila Giuberti de (2012)
Currently, the World Health Organization considers dengue the most important viral disease transmitted by mosquitoes and it is estimated that 50 million new infections occur each year worldwide. The global spread of dengue and the demand for rapid, specific and easy to perform diagnostic tests has increased the marketing of new tests. For a better use of these tools it is essential to evaluate them in different clinical, epidemiological and laboratory settings. The aim of this study was to evaluate the sensitivity of seven laboratory tests for dengue diagnosis. The sensitivities for the NS1 immunochromatographic tests were: 24,5% [16,2 to 34,4] for Dengue Duo (Bioeasy) and 29,8% [20,8 to 40,1] for Dengue NS1 Ag strip (Bio-Rad). The sensitivities of the NS1 ELISA tests were: 43,6% for Dengue NS1 ELISA Test (Bioeasy) [33,4 to 54,2] and 54,3% [43,7 to 64,6] for PlateliaTM Dengue NS1 Ag-ELISA (BioRad). The NS1 test that demonstrated greatest sensitivity in acute phase samples was PlateliaTM (54,3%). For all NS1 tests greater sensitivity was observed for serotype 1, when compared to the others serotypes. The sensitivity of PlateliaTM (BioRad) was negatively influenced by the presence of IgG. The sensitivity of the ELISA IgM tests ranged from: 27,1% [15,3 to 41,9] to 52,1% [37,2 to 66,7] in acute phase samples and from 72,9% [53,8 to 81,3] to 97,9% [88,9 to 99,9] in convalescent phase samples. Among all the tests evaluated, Dengue IgM ELISA Test (Bioeasy), in convalescent phase samples, showed the best performance. The sensitivity in acute phase samples was 76,6% [66,7 to 84,7] when Dengue NS1 Ag test PlateliaTM ELISA (BioRad) and Dengue IgM ELISA Test (Bioeasy) were combined. Our results suggest that NS1 tests may have different sensitivities, according to the viral serotypes, and in the presence of IgG antibodies. Furthermore, our results emphasize that the epidemiological profile of the population must be considered in the use and evaluation of dengue diagnostic tests